(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The theory of cognitive linguistics originates from cognitive psychology. This theory, by explaining complex linguistic phenomena from the depths of thinking, offers a new way of teaching Chinese as a foreign language.The introduction of cognitive linguistics in the teaching of Chinese as a foreign language, Chinese grammar can help international students understand and master complex knowledge of Chinese grammar and vocabulary, as well as lay the foundation for foreign students’ knowledge of Chinese language in communication